Financial Capital for Human Capital, Investment in Decent and Dignified Labor - Rodriguez, Luis Alfredo Jimenez; Mogollon, Javier Mauricio Garcia; Ortegon, Rene Vargas (Journal of Posthumanism, 2024)
Objective: To evaluate from a financial perspective the implementation of decent work as a condition for formal employment in the ESE Hospital Emiro Quintero Cañizares and consequently to be the genesis of the required framework of investment in plausible work for the development of human capital that leads to economic and social growth. Methodology: This study used a positivist paradigm with quantitative methodology and descriptive approach which consisted of phases: review of the state of the art, structural equations, instrument construction, validation by experts, survey diligence and data synthesis. Results: The outsourced population assigned to each union was determined, focusing on operating costs, and visualized through structural equations the needs of the referential units, their profile, number of positions and salary. Conclusions: Decent work conditions were strengthened, that is, having access to full and productive employment, having rights at work, having social protection guarantees and promoting social dialogue, which are productive development strategies that lead to the generation of quality jobs, sustaining and expanding formalization policies of the same, including a territorial perspective; the above, implies changes in the sustainable economic development model, which should be characterized by the existence of empowered human capital, relevant and committed to the assurance and provision of services with efficiency and human quality.